Life on the Urbach Edge - Ugur, Esma; Ledinský, Martin; Allen, Thomas G.; Holovský, Jakub; Vlk, Aleš; De Wolf, Stefaan (The journal of physical chemistry letters, 2022)
The Urbach energy is an expression of the static and dynamic disorder in a semiconductor and is directly accessible via optical characterization techniques. The strength of this metric is that it elegantly captures the optoelectronic performance potential of a semiconductor in a single number. For solar cells, the Urbach energy is found to be predictive of a material’s minimal open-circuit-voltage deficit. Performance calculations considering the Urbach energy give more realistic power conversion efficiency limits than from classical Shockley–Queisser considerations. The Urbach energy is often also found to correlate well with the Stokes shift and (inversely) with the carrier mobility of a semiconductor. Here, we discuss key features, underlying physics, measurement techniques, and implications for device fabrication, underlining the utility of this metric.